2020
DOI: 10.4103/aca.aca_255_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pectoral Nerve (PECS1) block with combined PECS1 and transversus thoracis muscle (TTM) block in patients undergoing cardiac implantable electronic device insertion – A pilot study

Abstract: Background: Pectoral nerve (PECS1) block has been used for patients undergoing cardiac implantable electronic device (CIED) insertions, however, PECS1 block alone may lead to inadequate analgesia during tunneling and pocket creation because of the highly innervated chest wall. Transversus thoracis muscle plane (TTM) block targeting the anterior branches of T2-T6 intercostal nerves can be effectively used in combination with PECS1 for patients undergoing CIED insertion. The present study hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 12 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…However, as the innervation of the chest wall is very complex, PECS I block alone may not provide complete analgesia. Arasu et al 4 reported that PECS I block alone may be insufficient for analgesia, especially during tunneling and pocket creation, and the combination of PECS I and transversus thoracic muscle plane block provided superior analgesia than PECS I block alone. However, visualization of the transversus thoracic muscle by ultrasound may be difficult because of its thin structure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as the innervation of the chest wall is very complex, PECS I block alone may not provide complete analgesia. Arasu et al 4 reported that PECS I block alone may be insufficient for analgesia, especially during tunneling and pocket creation, and the combination of PECS I and transversus thoracic muscle plane block provided superior analgesia than PECS I block alone. However, visualization of the transversus thoracic muscle by ultrasound may be difficult because of its thin structure.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in a few studies and case reports that some truncal blocks could provide adequate surgical anesthesia and postoperative analgesia in CIED insertion. [3][4][5][6][7][8][9] Pectoral nerve (PECS) blocks (PECS I and PECS II) were introduced by Blanco and were seen to provide effective analgesia after breast surgery. 10,11 The PECS I block is a single plane block that provides analgesia of the lateral surface of the breast and chest wall after local anesthetic applied between the fascia of the pectoralis major and minor muscles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the patients enrolled in the BRUISE CONTROL‐ 1 and 2 trials ( n = 1308), 26.8% of patients had moderate pain (VAS score 4−6), while 26.6% had severe pain (VAS score 7−10) 13 . PECs blocks were initially developed for thoracic and breast procedures and have now shown promise when used for CIED implantation in several case series 9–12,14 . The utilization of nerve blocks in CIED implantation has multiple benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, nerve blocks have been used to reduce periprocedural pain, intravenous sedation requirements, and possibly length of stay 8–14 . The PECS1 nerve block has previously been reported for CIED implantation.…”
Section: Introductionmentioning
confidence: 99%